Letter (copy) - McDonald, Florence
1937-02-19 011-0139-001 FEM/MT/595 Secretary's 19th February, 1937. The Private Secretary to Professor Catlin, 19, Glebe Place, CHELSEA, S.W.3. Dear Sir, Thank you for your letter of the 17th February, enclosing copies of Professor Catlin's letters to Monsieur Schevenels and Monsieur Blum. Sir Walter Citrine is at present attending an international meeting but on his return to London your letter will be placed before him. Yours faithfully, Private Secretary. 292/946/11/139(i)